FDI in the Balkans: the good, the bad and the ugly - Prelec, T (Ledizioni – LEDIpublishing, 2020)
2020 could be a crucial year for the Western Balkans. What are the factors contributing to Western Balkans instability in the age of Covid-19? Will the region continue to be ground for renewed geopolitical competition?